Kandungan Karbon Pada Serasah Excoecaria agallocha di Muara Sungai Tanggul, Desa Sungai Nibung, Kubu Raya - Mardianto, Tomi; Safitri, Ikha; Sofiana, Mega Sari Juane; Farhaby, Arthur Muhammad; Apriansyah, Apriansyah; Warsidah, Warsidah (Program Studi Ilmu Kelautan FMIPA Universitas Tanjungpura, 2024)
Mangroves play a vital role in maintaining environmental, providing habitat for various organisms, and protecting coastal areas from abrasion. In addition, mangroves function as carbon sinks, where a portion of the captured carbon used for energy, and the others stored in plant stuctures. Thus, mangroves significantly contribute to climate change mitigation through carbon sequestration. This study aims to determine the carbon content of mangrove litter from Excoecaria agallocha species in the estuary of Sungai Tanggul, Sungai Nibung Village. Kubu Raya, West Kalimantan. The types of litter measured include leaves, fruits, twigs, and flowers, which were collecter using litter traps. The results showed the total carbon content of the litter was 7.49 tons/ha/year. The largest contribution from leaves litter (5.49 tons/ha/year), followed by twigs (1.90 tons/ha/year), and fruits (0.10 tons/ha/year),while flowers had an insiginificant carbon content.